Analisis Nilai Tambah Rantai Pasokan (Supply Chain) Susu Sapi Di Desa Singosari Kecamatan Mojosongo Boyolali - Maharani, Maharani, Hafidh Munawir, S.T., M.Eng (2016)
Cow's milk is one type of food that has high nutritional and often consumed for most people to meet the nutritional needs every day. Cow's milk supply chain is a system arrangement related to the product flow, financial flow, and information flow within the distribution process started buying milk from cows, milking, until sold to consumers. The purpose of this study was to: determine the flow of product, financial, and information on cow's milk supply chain, calculate the added value gained from each chain in the supply chain cow's milk, and analyze the chain with the smallest value added and fix the chain in order to increase value added. Method in this research use descriptive method and Hayami method to analyze value added. Model cow's milk supply chain starting from suppliers cows, cattle breeders, collectors milk, milk cooling industry (KUD), the milk processing industry, and consumers. Analytical results from this study are: there are three streams that run in the supply chain of milk cows in the village of Singosari include product flow, financial flow, and the flow of information, which is the product flow runs less than optimal, the milk processing industry into a chain with the added value of the total of Rp 807.41 per liter and the breeder is the smallest value chain where to forward there are a few things that should be improved to increase the added value of cow's milk.